Implementation of the balanced score card as a benches for the performance assessment of Patut Patju Hospital - Linda Azizah; Sastrawan; Sabar Setiawan (Institute of Computer Science (IOCS), 2023)
This study aims to test and measure the performance of the Patut Patuh Patju Regional General Hospital in West Lombok using the Balanced Scorecard method. The approach used is mixed-methods research. This study uses secondary data to measure performance based on the four perspectives of the balanced scorecard, namely the financial perspective and the perspective of internal business processes. The population of employees at Patut Patju Hospital in West Lombok is 497 people, and the number of samples to be taken is 100 people. This research was conducted at Patut Patuh Patju General Hospital in West Lombok. After applying the balanced scorecard, the performance of the Patut Patuh Hospital in West Lombok is located in the